Risk of falls associated with drug therapy in hospitalized patients - Lemes Lobo Bittencourt, Vivian; Denise Endruweit Battisti, Iara; Aparecida Petri, Anieli; de Fátima Colet, Christiane; Miladi Fernandes Stumm, Eniva; Maria Loro, Marli; Roseli Winkelmann, Eliane (O Mundo da Saúde, 2020)
The risk of falls and the administration of medications are related to the safety of hospitalized patients. Thus, this study aimed to identify classes of drugs and drug interactions that increase the risk of hospital falls. This was a quantitative, cross-sectional study, in the southern region of Brazil, with 612 patients from inpatient units. Data were collected using a specific instrument for demographic data, Morse Scale and medical chart analysis from June to August 2015. In the univariate statistical analysis, absolute and relative frequencies were used and in the bivariate analysis, a chi-squared test with a level of 5% significance was used. 612 patients participated in the study, with use of drugs that act on the cardiovascular and nervous systems prevailing. The main classes of drugs related to high risk of falls were antiparkinsonian (76.2%) and calcium channel blockers (57.1%). The number of medications was also associated with a high risk of falling, present in 56.2% of patients using five or more drugs. 2,187 drug interactions were identified, of which 9.1% were potentiating the risk of falls, among the drugs involved in serious or contraindicated interactions there was a higher frequency among patients taking morphine (16.5%) and metoclopramide (6.0%). The most frequent serious interaction was morphine and tramadol (7.7%). It was observed that drugs frequently used by hospitalized patients are associated with an increased risk of falls and that the existence of potential drug interactions also can increase the risk of falls. Knowing the profile of the drugs used and their relationship with the risk of falls in the hospital environment helps administrators implement preventive actions.